Application of a training program to improve the levels of transformational leadership in third year high school students of the Héroes del 41 school in the city of Machala, Provincia del Oro - Herrera Salazar, Jacinto Fabricio (2020)
The scientific research that has been carried out is applied, of experimental design, which had as objective to demonstrate that the application of a training program, influences significantly improving the level of transformational leadership in the students of the third year of high school of the Héroes del 41 school. the city of Machala Province of Gold. The design of the research is experimental longitudinal cut. For the data collection a test was made to evaluate the transformational leadership level of the students, the population consisted of 48 students, who formed two groups with 24 students and the experimental group with 24 students; the instrument went through a process of validity and reliability before being applied. As for the program, six sessions were designed, which were developed in a time of two hours in which the students interacted, the pretest was applied first, and then the program was applied and the posttest was applied. The results obtained show first that the application of a training program influences significantly improving the level of transformational leadership in the students of the third year of high school at the Héroes del 41 school in the city of Machala Provincia del Oro, when it is obtained that in the post-test the value of p = 0.000 <0.05.